Recovery of β-carotene and astaxanthin from Phaffia rhodozyma biomass using aqueous solutions of cholinium-based ionic liquids - Mussagy, Cassamo U.; Farias, Fabiane O.; Bila, Niura M. [UNESP]; Giannini, Maria J.S.M. [UNESP]; Pereira, Jorge F.B.; Santos-Ebinuma, Valeria C. [UNESP]; Pessoa Jr, Adalberto (Elsevier, 2022)
The red yeast Phaffia rhodozyma is a natural source of high-added value carotenoids such as β-carotene and astaxanthin, widely used in the cosmeceutical, chemical, feed/food and pharmaceutical industries. This yeast is characterized by a rigid cell wall mainly composed of biopolymers, being required an appropriate design of downstream processing to recovery these intracellular carotenoids. In this sense, a biocompatible alternative for the selective recovery of β-carotene and astaxanthin from P. rhodozyma cells by using ionic liquids (ILs) was proposed. The performance of different cholinium-based ILs to permeabilize the cell wall and recovery intracellular carotenoids from P. rhodozyma wet biomass was evaluated and the operational conditions were optimized. The recovery yields of β-carotene and astaxanthin increased with the increment of alkyl chain length of the anion (cf., increase of relative hydrophobicity of ILs), being cholinium octanoate [Ch][Oct] the most efficient (50 wt% in water, 45 °C and 60 min). The stability of carotenoids in ILs as well as the mechanisms behind the recoveries have also been investigated. Afterwards, it was developed for the best IL solution an integrative platform for the recycling of the solvents (up to three successive cycles without any make up) and recovery of β-carotene and astaxanthin using bio-based solvents. The results demonstrate the efficiency of cholinium-based ILs for the recovery of β-carotene and astaxanthin (≈ 40% w/w) from P. rhodozyma in one-step extraction, reinforcing the aptitude of ILs for the recovery of intracellular biomolecules from microbial-based biomass.
Keywords: Astaxanthin; Carotenoids; Ionic liquids; Phaffia rhodozyma; Solid–liquid extraction; β-carotene